A chrysotile-based Fe/Ti nanoreactor enables efficient arsenic capture for sustainable environmental remediation. (1st March 2023) - Gao, Baolin; Liu, Kai; Li, Fangbai; Fang, Liping
Highlights: A novel chrysotile Fe/Ti nanoreactor has been developed for arsenic capture. This nanoreactor exhibits a strong selectivity towards As in soil solution. The longevity of the nanoreactor is considerably greater than commercial products. Environmental sustainability and cost-efficiency of the nanoreactor are revealed. Abstract: Iron-based materials for arsenic (As) immobilization in practical groundwater and soil remediation suffer from a low removal capacity and an insufficient long-term stability. Herein, a unique chrysotile-based nanoreactor has been developed by incorporating iron/titanium oxides into the cylindrical cavity of chrysotile (TiFe-Chy), providing sufficient internal reaction sites for As immobilization. Results reveal that the adsorption capacities of TiFe-Chy for As(III) and As(V) are considerably higher than the commonly used amendments, i.e., layered double hydroxide (LDH) and Phoslock®, respectively. More importantly, TiFe-Chy exhibits a strong anti-interference capability of As immobilization in soils compared to those commercial products due to this unique incorporation approach. Fixed-bed leaching experiments indciate that this TiFe-Chy nanoreactor can efficiently decrase the As(III) and As(V) concentrations by 81.8–87.3% within a period of ten years, significantly improving the long-term stability of As immobilization in soils. Life cycle assessment analysis reveals that TiFe-Chy can reduce negative environmental impacts (such as carbon emissions), resulting in a low cost for soils and groundwater remediation. The findings of this work open a new avenue for sustainable heavy metal(loid)s remediation in groundwater and soils. Graphical abstract: Image, graphical abstract